Extensões ao protocolo de comunicações EPCGloboal para tags Classe 1 utilizando autenticação com criptografia de baixo custo para segurança em identificação por radiofreqüência - Mota, Rafael Perazzo Barbosa (2006)
EPCGlobal communication protocol for RFID (Radio Frequency Identification) does not ensure security and privacy for its system users. This fact makes possible several kinds of security problems on RFID technology usage justifying that security mechanisms should be added to communication protocol preserving the existing standards. This work proposal is based on communication authentication usage making use of low-cost cryptography with the TEA algorithm. The proposed mutual authentication mechanism was specified and proved using BAN logic. All protocol specification has considered the EPCGlobal standard for Class 1 tags as base adding security and privacy extensions to data communication to get protection against several attacks. The results from this work include an authentication protocol formal specification with cryptography allowing this way the protocol standardization using as base the current Class 1 protocol.